Averaging Scheme for the Aerosol and Carbon Detection Lidar Onboard DaQi-1 Satellite - Cao, Xifeng; Zhang, Xingying; Zhang, Lu; Zhou, Minqiang; Jiang, Yuhan; Liu, Jiqiao; Cheng, Tiantao; Fan, Chuncan; Chen, Cheng; Chen, Lin (IEEE transactions on geoscience and remote sensing, 2024)
Atmospheric carbon dioxide (CO 2 ) is the primary anthropogenic driver of climate change, accounting for more than half of the total effective radiative forcing (ERF). Active remote-sensing technique using differential absorption Lidar (DIAL) is recognized as the most promising remote sensing means for atmospheric carbon dioxide measurements. The Aerosol and Carbon Detection Lidar (ACDL) instrument onboard the DQ-1 is dedicated to quantifying the global spatial distribution of atmospheric CO 2 . To meet the requirement of accuracy and precision, a reasonable averaging scheme for ACDL measurements is needed to minimize the effect of random noise of observations on CO 2 retrievals. In this study, three averaging schemes were conducted in the retrieval process: averaging of CO 2 columns (AVX), averaging of differential absorption optical depth (AVD), and averaging of signals (AVS). The performances were compared at three representative sites. The experiments were first carried out on simulations. The results show that the optimal size of the averaging window is 50 km, corresponding to an averaging of measurements over 150 pulse pairs. In addition, the AVX and AVD schemes are less affected by altitude variations and can be applied to surfaces with moderate and severe topographic variation, such as hills and mountains. Whereas the AVS method is more suitable for surfaces with slight topographic variation, such as oceans, plains, and terraces. Furthermore, the ACDL observations were also retrieved by applying three averaging schemes and validated against ground-based TCCON measurements at Xianghe station. The AVS scheme exhibits better performance than the AVX and AVD methods with the lowest biases of less than 0.5 ppm, which is consistent with the simulation results.